2019
DOI: 10.1111/aas.13360
|View full text |Cite
|
Sign up to set email alerts
|

Infections and outcomes after cardiac surgery—The impact of outbreaks traced to transesophageal echocardiography probes

Abstract: Background Infections are a frequent complication of cardiac surgery. The intraoperative use of transesophageal echocardiography (TEE) may be an underrecognized risk factor for post‐operative infections. The aim of this study was to investigate infection rates and outcomes after cardiac surgery in a nationwide cohort, especially in relation to periods where surface damaged TEE probes were used. Methods This was a retrospective, observational study at Landspitali University Hospital. All consecutive cardiac sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
0
7
1
Order By: Relevance
“…We were not surprised at this result. One study found that the bloodstream infection rate was 2.8% after cardiac surgery [28]. Therefore, for some immunocompromised patients, it is not strange for a bloodstream infection to cross the blood – retinal barrier into the eye after cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…We were not surprised at this result. One study found that the bloodstream infection rate was 2.8% after cardiac surgery [28]. Therefore, for some immunocompromised patients, it is not strange for a bloodstream infection to cross the blood – retinal barrier into the eye after cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Two publications in 2019 implemented the TOE transducers in cross-contamination resulting in high mortality [41,42]. Noel et al reported on the outbreak of extended-spectrum B-lactamase (ESBL) producing Enterobacter cloacae among cardio-thoracic surgical patients [41].…”
Section: Outbreaks and Case Reports Of Potential Infection Transmissionmentioning
confidence: 99%
“…Despite negative swabs of the TOE transducer, its removal from use resulted in the cessation of reported cases. The second study investigated infectious complications following the use of TOE transducers during cardiac surgery [42]. Of the 973 patients, 3.4 % became infected with Klebsiella oxytoca, Pseudomanas aeruginosa or endocarditis with Enterococcus faecalis, with all three pathogens cultured from TOE transducers post-decontamination.…”
Section: Outbreaks and Case Reports Of Potential Infection Transmissionmentioning
confidence: 99%
See 2 more Smart Citations